A New Look for the Jewish Past: Historicism, Authenticity, and Fantasy in E. M. Lilien's Bible Art. Issue 1 (2nd January 2023) - Miller, Eva
Abstract: In the multivolume Bücher der Bibel (1908–12), Jewish artist Ephraim Mose Lilien imagined a glorious Jewish past that resonated with Zionist discourses of spiritual and artistic revival. He visualized this past in part through appropriating iconography from ancient Egypt and Mesopotamia. The significance of Lilien's historicism must be understood in the context of a culture conflicted about the relationship between the Bible and the Middle Eastern past, at a time when an association between German imperial power and the ancient Middle East was ubiquitous in popular media and promoted at the highest levels of the state.